Tablet computers in Philippine public schools: school-level factors that influence technology management and use. Issue 1 (1st January 2019) - Lumagbas, Jedaiah Joel; Smith, Wally; Care, Esther; Scoular, Claire
ABSTRACT: Many developing countries are investing in large-scale initiatives to deploy information and communications technology in schools. However, merely equipping schools with hardware and software does not guarantee that the technology is used effectively to improve learning outcomes. This study aims to identify factors that influence the use of technology in schools in a developing-country context. It investigates this through a multiple-case study of the Australian AID tablet computer programme in the Philippines, in which 1000 tablets were given to nine public schools for student use. Focusing specifically on the impact at a whole-school level, the study revealed factors affecting outcomes that were specific to a developing-country context, as well as confirming the relevance of more general factors identified in the literature. The study also brings to light tablet-specific benefits and issues in this context. These results have implications for the effective school-level implementation of technology programmes in developing countries. Recommendations that proceed from these are presented for policy-makers and school administrators looking to use these devices in schools.